2014
DOI: 10.1002/ange.201403607
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Carboannulation with Allylsilanes

Abstract: The first catalytic asymmetric carboannulation with allylsilanes is presented. The enantioselective [3+2] annulation is catalyzed using a Sc(III)-indapybox complex with tetrakis-[3,5-bis(trifluoromethyl)phenyl]-borate (BArF) to enhance catalytic activity and control stereoselectivity. Functionalized cyclopentanes containing a quaternary carbon are derived from alkylidene oxindole, coumarin, and malonate substrates with high stereoselectivity. The enantioselective 1,4-conjugate addition and enantioselective la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…An initial investigation by our group reported the formation of an NaOTf precipitate, characterized by 19 F NMR spectroscopy and FAAS (Figures S1 and S2). It was also noted that conditions using NaBArF disrupt the formation of an inactive catalyst complex (Figures S4 and S5), both supporting our hypothesis, wherein Sc­(OTf) 2 / L1 /BArF acts as the active catalyst complex. Our initial foray into the structure and mechanism of the scandium-catalyzed asymmetric [3 + 2] annulation reaction highlighted several spectroscopic features indicating the complexity of the system.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…An initial investigation by our group reported the formation of an NaOTf precipitate, characterized by 19 F NMR spectroscopy and FAAS (Figures S1 and S2). It was also noted that conditions using NaBArF disrupt the formation of an inactive catalyst complex (Figures S4 and S5), both supporting our hypothesis, wherein Sc­(OTf) 2 / L1 /BArF acts as the active catalyst complex. Our initial foray into the structure and mechanism of the scandium-catalyzed asymmetric [3 + 2] annulation reaction highlighted several spectroscopic features indicating the complexity of the system.…”
supporting
confidence: 80%
“…Asymmetric metal catalysis has emerged as an important tool for the development of chiral molecules with high molecular complexity with simple operational one-pot procedures, atom efficiency, and mild reaction conditions. We have reported the asymmetric scandium­(III)-catalyzed [3 + 2] annulation of alkylidene oxindoles and isatins with allylsilane and allenylsilane nucleophiles. The scandium­(III)–PyBox/BArF (PyBox: pyridine-2,6-bis­(oxazoline); BArF: tetrakis­[3,5-bis­(trifluoromethyl)­phenyl]­borate) complex is a powerful catalyst system, demonstrating robust activity in a variety transformations and with potential application toward further synthetic applications. However, our previous studies provided an incomplete picture of the active catalyst complex that we were interested in investigating further. We elected to study the Sc­(OTf) 2 -( R , S )-inda-PyBox ( L1 )/BArF complex using the [3 + 2] annulation reaction of allylsilanes 2a with alkylidene oxindole 1a (Scheme ).…”
mentioning
confidence: 99%
“…Franz has extended this carboannulation methodology to include alkylidene oxindoles 1374 as electrophiles, utilizing a ScCl 3 /( R , S )- 1337 /NaBARF catalytic system, to give the corresponding spirooxindoles 1375 in up to 99% yield and 99% ee ( Scheme 407 ). 487 …”
Section: Bis(oxazoline) Ligandsmentioning
confidence: 99%
“…For instance, in 2014 Franz and co-workers presented a chiral Sc(III) complex-catalyzed asymmetric [3 + 2] annulation of allylsilanes 149 and methyleneindolinones 18 through a Michael/1,2-silyl shift/cyclization process (Scheme 38). 93 They found that a 10 mol % loading of the chiral PyBOXderived Sc(III) complex generated in situ from (R,S)-indaPyBOX 150, Sc(OTf) 3 , and NaBArF smoothly mediated this annulation and provided an array of functionalized spirooxindolic cyclopentanes 151 in good to excellent yields and selectivities. Notably, the additive NaBArF might play two roles in the annulation process: one is to enhance the catalytic activity by forming a cationic (R,S)-indaPyBOX•Sc-(OTf) 2 BArF complex, and the other is to facilitate the generation of a transient β-silyl carbocation.…”
Section: Acs Catalysismentioning
confidence: 99%